Anatomy of resuscitative care unit: expanding the borders of traditional intensive care units. Issue 6 (2nd April 2019) - Leibner, Evan; Spiegel, Rory; Hsu, Cindy H; Wright, Brian; Bassin, Benjamin S; Gunnerson, Kyle; O'Connor, James; Stein, Deborah; Weingart, Scott; Greenwood, John C; Rubinson, Lewis; Menaker, Jay; et al.
Abstract : Resuscitation lacks a place in the hospital to call its own. Specialised intensive care units, though excellent at providing longitudinal critical care, often lack the flexibility to adapt to fluctuating critical care needs. We offer the resuscitative care unit as a potential solution to ensure that patients receive appropriate care during the most critical hours of their illnesses. These units offer an infrastructure for resuscitation and can meet the changing needs of their institutions.